Niveles de ventas en la Farmacia Cruz Azul ubicada en Babahoyo en las calles Pedro Carbo entre 5 de Junio y 10 de Agosto - Rodríguez Gil, Carlos Daniel (2021)
The case study was carried out at a point of sale of the Cruz Azul Pharmacy in the city of Babahoyo. The commercial point is dedicated to the commercialization of various pharmaceutical products and supplies; pharmacy that was influenced by the health crisis generated by the Covid-19 pandemic, causing a significant variation in sales revenue. The objective of the case was to evaluate the economic income of the pharmacy, to know the risk factors that determine the sales income, in addition to comparing the sales of 2019-2020, and to determine the economic situation of the company. The methodology used had a quali-quantitative approach accompanied by the types of exploratory and descriptive research, which allowed to collect, analyze and interpret the information on the issue raised. The inductive and deductive methods were applied together with the techniques of interview and direct observation, through a questionnaire on human talent and the review of income. The findings were: the increase in sales from March to June; The pharmacy does not have a contingency plan for external situations, difficulties in the sales process due to excessive demand for products, inadequate inventory management and the application of sales strategies. In conclusion, the Cruz Azul Pharmacy analyzed was not prepared to meet the excessive demand for medicines as a result of the pandemic, therefore, they had to adapt to the pandemic and improve sales strategies; that is to say, turn the crisis into opportunity.